What parameters influence the effect of cold-water immersion on muscle soreness? An updated systematic review and meta-analysis - Batista, N. P.; de Carvalho, F. A.; Machado, A. F.; Micheletti, J. K.; Pastre, C. M. (Clinical Journal of Sport Medicine, 2023)
Objective: Our objective was to determine the efficacy of cold-water immersion (CWI) on the management of muscle soreness to identify the impact of immersion time, water temperature, CWI protocol, and type of exercise on this outcome.